Monitoring temporal trends of dioxins, organochlorine pesticides and chlorinated paraffins in pooled serum samples collected from Northern Norwegian women: The MISA cohort study - Xu, Shanshan; Hansen, Solrunn; Rautio, Arja; Järvelin, Marjo-Riitta; Abass, Khaled; Rysä, Jaana; Palaniswamy, Saranya; Huber, Sandra; Grimalt, Joan O.; Dumas, Pierre; Odland, Jon Øyvind (Environmental Research, 2022)
The ubiquitous presence of legacy and emerging persistent organic pollutants (POPs) in the environmental matrices poses a potential hazard to the humans and creating public health concerns. The present study aimed to evaluate dioxins, dioxin-like polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs) and chlorinated paraffins (CPs) concentrations in serum of women (postpartum, pregnant and non-pregnant) from Northern Norway to better understand their exposure and contamination status as well as temporal trends across 2007–2009 (MISA 1) to 2019 (MISA 2). Sixty-two blood samples from the MISA 1 cohort and 38 samples from MISA 2 were randomly selected in this study (n = 100). Ninety samples from postpartum (MISA 1) and pregnant women (MISA 2) were randomly combined into 9 pools, with 9–11 individual samples contributing to each pool keeping the groups of pregnant and postpartum women. Remaining 10 samples from non-pregnant women (MISA 2) were allocated into separate group. Geometric mean, minimum and maximum were used to describe the serum concentrations of pooled POPs in MISA cohort. Mann-Whitney U test and independent sample t-test were applied for trend analysis of blood levels of POPs between MISA 1 and MISA 2. We found the serum concentrations of selected POPs in this study to be at lower range. Serum concentrations of dibenzo-p-dioxins (PCDDs) (p = 0.010), polychlorinated dibenzofurans (PCDFs) (p = 0.002), dioxins-like PCBs (p = 0.001), hexachlorobenzene (HCB) (p < 0.001) and p,p’-dichlorodiphenyldichloroethylene (p,p’-DDE) (p = 0.002) were decreased between the studied time. In contrast, the serum concentrations of medium chain chlorinated paraffins showed an increasing trend between 2007 and 2009 and 2019 (p = 0.019). Our findings report a particular concern of emerging contaminant medium chain chlorinated paraffin exposure to humans. Future observational studies with repeated measurements of chlorinated paraffins in general populations worldwide and large sample size are warranted. The ...